A device for human ultrasonic echolocation - Sohl-Dickstein, Jascha (IEEE Trans Biomed Eng, 2015)
OBJECTIVE: We present a device that combines principles of ultrasonic echolocation and spatial hearing to provide human users with environmental cues that are 1) not otherwise available to the human auditory system and 2) richer in object, and spatial information than the more heavily processed sonar cues of other assistive devices. The device consists of a wearable headset with an ultrasonic emitter and stereo microphones with affixed artificial pinnae. The goal of this study is to describe the device and evaluate the utility of the echoic information it provides. METHODS: The echoes of ultrasonic pulses were recorded and time-stretched to lower their frequencies into the human auditory range, then played back to the user. We tested performance among naive and experienced sighted volunteers using a set of localization experiments in which the locations of echo-reflective surfaces were judged using these time stretched echoes. RESULTS: Naive subjects were able to make laterality and distance judgments, suggesting that the echoes provide innately useful information without prior training. Naive subjects were generally unable to make elevation judgments from recorded echoes. However trained subjects demonstrated an ability to judge elevation as well. CONCLUSION: This suggests that the device can be used effectively to examine the environment and that the human auditory system can rapidly adapt to these artificial echolocation cues. SIGNIFICANCE: Interpreting and interacting with the external world constitutes a major challenge for persons who are blind or visually impaired. This device has the potential to aid blind people in interacting with their environment.